Prognostic value of left atrioventricular coupling index (LACI) in pre- and post-menopausal women : from the multi-ethnic study of atherosclerosis (MESA). (4th February 2022) - Pezel, T; Michos, E; Varadarajan, V; Shabani, M; Ambale Venkatesh, B; Vaidya, D; Kato, Y; De Vasconcellos, H; Heckbert, S; Wu, C; Post, WENDY; Bluemke, D; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. BACKGROUND: Although endogenous sex hormones influence both left atrial (LA) and left ventricular (LV) structure in peri-menopausal women, no study has ever evaluated the interaction between sex hormones levels and the left atrioventricular coupling. PURPOSE:  This study aimed to assess the prognostic value of a left atrioventricular coupling index (LACI) in pre- and post-menopausal women without history of CVD at baseline. METHODS: In all women participating in the Multi-Ethnic Study of Atherosclerosis (MESA) with baseline cardiovascular magnetic resonance (CMR) study, LACI was measured as the ratio of the LA end-diastolic volume divided by the LV end-diastolic volume. Cox proportional hazard models were used to assess the association between LACI and the outcomes of atrial fibrillation (AF), heart failure (HF), coronary heart disease (CHD) death, and hard CVD defined by myocardial infarction, resuscitated cardiac arrest, stroke, or CHD death. In multivariable analyses, the associations between LACI and the time-to-event were evaluated, adjusting for demographics, traditional cardiovascular risk factors, menopausal status and sex hormone levels. RESULTS: Among the 2, 087 women (61.2 ± 10.1 years), 485 cardiovascular events were observed during mean follow-up period of 13.2 ± 3.3 years. Greater LACI was independently associated with AF (HR 1.70; 95% CI [1.51-1.90]), HF (HR 1.62; 95% CI [1.33-1.97]), CHD death (HR 1.36; 95% CI [1.10-1.68]), and hard CVD (1.30; 95% CI [1.13-1.51], all p < 0.001). Adjusted models with LACI showed significant improvement in model discrimination and reclassification compared to currently used standard models to predict the incidences of AF (C-statistic: 0.82 vs. 0.79; NRI = 0.325; IDI = 0.036), HF (C-statistic: 0.84 vs. 0.81; NRI = 0.571; IDI = 0.023), CHD death (C-statistic: 0.87 vs. 0.85; NRI = 0.506; IDI = 0.012), and hard CVD (C-statistic: 0.78 vs. 0.76; NRI = 0.229; IDI = 0.012). The prognostic value of LACI was homogeneous in both pre- and post-menopausal women with a better discrimination and reclassification compared to individual LA or LV parameters. CONCLUSIONS: In a multi-ethnic population of pre- and post-menopausal women, LACI is an independent predictor of HF, AF, CHD death and hard CVD. In both pre- and post-menopausal women, LACI has an incremental prognostic value to predict cardiovascular events over traditional risk factors and sex hormone levels. ClinicalTrials.gov Identifier: NCT00005487